The Importance of The International Assessment Programs Pisa and Timss - Fazliddin Botirovich Kurbonov (Academia One Publishing, 2023)
This article reflects information about the importance of the international assessment programs PISAand PIRLS, which are foreign experience, in improving the quality of education and achieving efficiency.
Keywords: assessment; PISA; PIRLS; TIMSS